Pengaruh Metode Latihan Variasi Menggunakan Raket Tenis Lapangan Terhadap Keterampilanpassing Sepak Takraw Pada Atlet PSTI Sumbawa Besar Tahun 2022 - Subakti dan Hermansyah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The practice of using a tennis racket on passing skills is a very suitable exercise to strengthen first ball control, so that when you counterattack against the opponent it can be done easily. Exercise using this court tennis racket can also hone the resistance of the feet, so that they can hold the ball well according to what they want. PSTI Sumbawa Besar athletes still has many weaknesses in ball control when passing so researchers want to research PSTI Sumbawa Besar athletes in controlling the ball when passing at takraw football games, at a match, especially in Sumbawa Besar. The purpose in this study is to find out the Influence of Variation Exercise Methods Using Court Tennis Rackets on Takraw Football Passing Skills in Large Sumbawa PSTI Athletes in 2022. The research design used is the static group pretest-postest design experimental research. This type of research is to use research by providing treatment (treatment), in the form of variation training methods using a court tennis racket against takraw football passing skills, this study uses intsrumen, namely the takraw football passing test, so that the research sample uses the entire population to be used as a research sample, namely all 20 Large Sumbawa PSTI Athletes with sampling techniques using population study techniques. The results of the study and analysis of data conducted using statistical formulas showed that the value of t-count is greater than t-table, (3,482>2,093) thus the value of